(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The purpose of this study was to culturally adapt the items of Bayley Scales of Infant Development?II (BSID?II) for administration upon Bangladeshi infants. The adaptation procedure was conducted by following four steps: (i) field survey on normative sample, (ii) national expertise opinion, (iii) international expertise consultancy and (iv) picture sensitivity review. The culture based problems of the original BSID?II were identified from the initial field survey. Major problems identified by the examiners were unfamiliarity of the children with the items (pictures, words and materials). These assessments were evaluated by the national and international consultants. The uncommon items were changed to culturally recognizable ones while Bangla words were replaced to make the test culture?fair. At last, the adapted test was given to 22 healthy children to assess picture sensitivity of the test and found suitable where the infants attentively responded to the items. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20099 Dhaka Univ. J. Biol. Sci. 23(2): 187-195, 2014